Debris management after earthquake incidence in ancient City of Ray - L. Askarizadeh; A.R. Karbassi; M.B. Ghalibaf; J. Nouri (Global Journal of Environmental Science and Management)
Ancient City of Ray, located at the southern urban part of Tehran province, is one of the best recognized civilization sites in the world. In this study, the past earthquake incidence in Ray was reviewed using hazards united states tool as a geographic information system-based natural hazard analysis tool. hazards united states tool was chosen to estimate the damage on structural and non-structural elements during various earthquake scenarios with magnitudes of 4.5, 6 and 7.5 on the Richter scale in Ray City. Earthquake magnetitudes of 4.5, 6 and 7.5 would severely damage 49, 72 and 82% of buildings, respectively. The number of casualties was estimated to be in the range of 558 to 2220  people. It was also computed that 93, 197 and 331 km3 of debris would be produced at 4.5, 6 and 7.5 Richter earthquake, respectively. Subsequently, Arc-GIS was used to find out the best route from the affected areas to the temporary disposal locations and to allocate the required number of heavy equipments and manpowers for debris disposal planning. A set of factors, including diversity of the existing wastes, separation of the recyclable wastes, and allocation of the best place and route for debris disposal in the shortest time and with the shortest distance in the street network, were presented and considered in the analyses. Finally, it was concluded that debris management is not only a logistic activity, but also it is an inseparable part of the post-accident recovery process.